Experimental Methods for Membrane Applications in Desalination and Water Treatment (IWA Publishing, 2024)
Water quality is a critical issue for the water industry today, and membrane filtration a highly effective treatment used to provide clean water for the global population. Experimental processes are being developed for assessing fouling, scaling, performance and modelling of membrane systems, and research is needed to further improve the sustainability and feasibility of these technologies, and to mitigate the challenges of water scarcity for billions of people, particularly in developing countries. This book aims to address this vital issue by bringing together experts in the field to share their learning, including: Membrane processes: microfiltration (MF), ultrafiltration (UF), reverse osmosis (RO), forward osmosis (FO) and membrane distillation (MD); Particulate fouling: silt density index (SDI), modified fouling index (MFI-0.45 and MFI-UF); Inorganic fouling and scaling: assessment, characterization tools and mitigation; Organic fouling: size exclusion chromatography (LC-OCD), fluorescence spectroscopy (FEEM) and transparent exopolymer particles (TEP); Biological fouling: genomic tools, bacterial growth potential (BGP) of seawater and low-nutrient water and optical coherence tomography (OCT); General applications: membrane autopsy and computational fluid dynamics (CFD) modelling. This book will be an important resource for undergraduate and graduate engineering students and researchers, academics, plant operators, consultants, professionals and practitioners in the water sector.